Active Channel Loss, Reed Canary Grass expansion, and Nutrient-Enriched Groundwater in the Lower Chippewa River in West-central Wisconsin - Moothart, Emily; Nesbit, Scott; Faulkner, Douglas (My University, 2017)
Maps constructed from aerial photographs dating to 1938 along a 50-km section of the Lower Chippewa River (LCR) in western Wisconsin document a decline of active-channel area exceeding 25%. This loss in channel area has occurred despite no detectable change in stream hydrology. Much of the loss seems instead due to the stabilization of lateral bars by reed canary grass (RCG), a significant invasive wetland species in the Upper Midwest. GPS surveys of RCG patches along the river indicate that RCG-stabilized bars account for as much as 100% of the main channel loss that occurred during the main period of RCG invasion. Why RCG invaded the channel during this time period is unknown, but one hypothesis is that it is coincident with the expansion of center-pivot irrigation on nearby cropland, which led to groundwater discharge into the river enriched in plant-available nutrients.
Color poster with text, photos, graphs, and charts.
Keywords: Active channel loss; Stream hydrology; Reed canary grass; Lower Chippewa River; Posters